This Is My Body: The Saving Knowledge of Suffering Flesh in Flannery O'connor's Wise Blood - DeCoste, D. Marcel (Religion & literature, 2017)
Taking up O'Connor's controversial first novel, this essay deals with Wise Blood's, focus on, and often grotesque treatment of, the human body. Noting the unsightly cast and cruel fate the body receives in this book, many critics have argued that Wise Blood offers a Manichean contempt for the flesh and presents the human body as something repellent, valueless and unredeemable. By contrast, the present study argues that O'Connor's novel in fact champions the intuitions of the flesh and affirms the potential efficacy, in suffering, of its incarnate wisdom. This paper seeks to demonstrate that the text's physical horrors do not oppose, but in fact help express the optimism of, Christian redemption. They do so as they enact what Wise Blood treats as the body's inborn knowledge of the person's call to devotion, atonement, and salvation, to a bodily participation in the saving travails of Christ. O'Connor's text forcefully argues that we know in our very flesh our need and our eligibility for eternal life, a life which can never be disentangled from our status as physical creatures but is purchased, first by Christ and then by the penitent, through corporeal sacrifice. Despite his sins and attempts at blasphemy, O'Connor's protagonist, Hazel Motes, is in the end moved by the wise blood of her title. What this blood teaches is that salvation works through our unavoidable suffering. Haze-self-blinded and mortifying his flesh with glass and barbed wire-certainly undergoes gruesome trials. But in O'Connor's decidedly sacramental world, that suffering enjoined by the flesh offers redemption for him insofar as it can achieve communion with the broken body of the Jesus Haze has sought and failed to deny. Ultimately, in a world made redeemable by that holy body's suffering, the earthly body of Wise Blood teaches both the human need for salvation and the penitential path to it.